2003
DOI: 10.2139/ssrn.373940
|View full text |Cite
|
Sign up to set email alerts
|

Internationalisation of High-Tech Start-Ups and Fast Growth - Evidence for UK and Germany

Abstract: NON-TECHNICAL SUMMARYIn recent years, much of the debate of policy makers, business academics and practitioners alike has centred on the nature and implications of the increasing importance of trans -and multi-national, ec onomic activity. Globalisation, the phenomenon of increasing economic interdependence across n ational borders, is believed to be particularly pertinent to hightechnology industries. These sectors are commonly characterised by high costs for research and development, decreasing product and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
1
25
2
1
Order By: Relevance
“…While some studies have found no systematic relationship to exist between firm size and growth (Wagner, 1992) still other have actually found a positive relationship (Burgel, Fier, Licht and Murray, 2000). Only a few studies have found have results similar to the U.S. (Almus and Nerlinger, 2000;and Harhoff, Stahl and Woywode, 1998).…”
Section: Has the Firm Size-growth Relationship Changed?mentioning
confidence: 97%
“…While some studies have found no systematic relationship to exist between firm size and growth (Wagner, 1992) still other have actually found a positive relationship (Burgel, Fier, Licht and Murray, 2000). Only a few studies have found have results similar to the U.S. (Almus and Nerlinger, 2000;and Harhoff, Stahl and Woywode, 1998).…”
Section: Has the Firm Size-growth Relationship Changed?mentioning
confidence: 97%
“…Burgel et al (2008) menemukan bahwa kecanggihan teknologi produk dan pengalaman pengusaha memilki dampak positif pada pertumbuhan. Selain itu, inovasi juga merupakan tekanan dalam perningkatan pertumbuhan.…”
Section: Pendahuluanunclassified
“…All firms are less than 10 years old, and classified as start-ups (Burgel et al 2000), with an average age of 3.5 years and a median age of 3. All firms have developed a software product, which is being trialled by a number of customers, with one exception.…”
Section: Profile Of Sample Firmsmentioning
confidence: 99%
“…(2) What are the resourcing implications of adopting cloud computing?, and (3) Have resourcing techniques used by founders of new firms changed in response to disruptive technological change? The novelty of this research is that we investigate direct resourcing implications of the 2 We adopt Butchart's (1987) broad definition of high technology firms, and all ventures in our sample fulfil the definition of start-ups provided by Burgel et al (2000), as independently held firms younger than 10 years operating in a high technology sector.…”
Section: Introductionmentioning
confidence: 99%